Antidiabetic Effect of an Active Components Group from Ilex kudingcha and Its Chemical Composition. (4th March 2012) - Song, Chengwu; Xie, Chao; Zhou, Zhiwen; Yu, Shanggong; Fang, Nianbai
Abstract : The leaves of Ilex kudingcha are used as an ethnomedicine in the treatment of symptoms related with diabetes mellitus and obesity throughout the centuries in China. The present study investigated the antidiabetic activities of an active components group (ACG) obtained from Ilex kudingcha in alloxan-induced type 2 diabetic mice. ACG significantly reduced the elevated levels of serum glycaemic and lipids in type 2 diabetic mice. 3-Hydroxy-3-methylglutaryl coenzyme A reductase and glucokinase were upregulated significantly, while fatty acid synthetase, glucose-6-phosphatase catalytic enzyme was downregulated in diabetic mice after treatment of ACG. These findings clearly provided evidences regarding the antidiabetic potentials of ACG from Ilex kudingcha . Using LC-DAD/HR-ESI-TOF-MS, six major components were identified in ACG. They are three dicaffeoylquinic acids that have been reported previously, and three new triterpenoid saponins, which were the first time to be identified in Ilex kudingcha . It is reasonable to assume that antidiabetic activity of Ilex kudingcha against hyperglycemia resulted from these six major components. Also, synergistic effects among their compounds may exist in the antidiabetic activity of Ilex kudingcha .